Coaching models: a brief exploration - McConnell, C. (New Studies in Athletics, 2016)
Models are useful to describe, analyse, evaluate and possibly predict what could happen in future situations. In coaching they can be helpful for understanding different aspects of the process even if, as two-dimensional descriptions, their capacity to explain its full complexity is limited. Coaching models take two basic forms: a `model for', which is an idealistic conception of practice, and a 'model of, formed from a deductive process based on an analysis of practice. This review of the current literature, intended by the author as a starting point for practicing coaches who seek a deeper understanding of their craft, begins with consideration of the early 'models for' of Franks et al and Fairs, who approach the subject as a process. It expands on these by describing various works of Lyle before turning to an examination of the views of Cote et al and Saury Et Durand, who suggest the alternative 'model of approach. It then considers the sociological / pedagogical approach of a number of authors who view coaching as a 'social and learning enterprise'. It concludes with the author's assessment of the models most likely to offer value in coaching practice.